Agoramétrie's Trunk Questions & Moscovici Social Representation's Core – More than Just Similarities. Issue 1 (October 2017) - van Meter, Karl M.
Thirty years of almost annual Agoramétrie surveys of opinions in France on social conflicts have shown the existence of a very stable two-dimensional structure with a "closure" / "openness" axis and a second "emotional" axis. These same results also show the existence of "trunk questions" which systematically appear in these surveys. On the other hand, in social representation, Serge Moscovici and his colleagues have shown through the method of "associated words", among others, that there is a very stable "core" or "nucleus" of social representations that generates and largely determine all the others. In this article, we present these two approaches and their results, and show that the set of "trunk questions" and the "heart" of social representations are more than just similar and perhaps identical.